Oxygen of bottom water samples from cruises conducted in 2020, 2021, and 2022 in Western Norwegian fjords - Mattia Ferraro; Bjørg Risebrobakken; Irina Polovodova Asteman; Elin Darelius; Amandine Tisserand; Natalya Gallo; Anne Gro Vea Salvanes (PANGAEA, 2025)
Bottom water samples were analysed in Bergen (Norway) using and ICP-OES Thermo Scientific iCAP 7600 to measure oxygen in seawater (umol/kg) from cruise conducted in 2020 (KB2020603), 2021 (KB2021605) and 2022 (KB2022602).
In: Ferraro, M et al. (2025): Dissolved oxygen concentration, trace elements concentration, carbon isotope composition and foraminifera assemblages data from Western Norwegian fjords [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982538